Kedudukan Balai Harta Peninggalan (BHP) dalam Mengurus dan Menyelesaikan Harta Peninggalan Tidak Terurus: Studi Kasus : Kantor Balai Harta Peninggalan (BHP) Medan - Inge Ruth Melati Br Ginting; Hasim Purba; Suprayitno (Jurnal Hukum Lex Generalis, 2026)
Unadministered estates create legal uncertainty if left unmanaged. The Balai Harta Peninggalan (BHP) is authorized to administer and settle such estates to protect heirs and related parties. This study uses an empirical juridical approach with data from literature and interviews at BHP Medan. The results show that BHP acts as a state representative until lawful heirs are identified, working with courts, notaries and other institutions. Challenges include limited information on heirs, low public awareness of BHP’s role and administrative obstacles. Therefore, improved inter-agency coordination, public outreach and stronger regulations and work mechanisms are needed to optimize estate administration and ensure legal certainty.